Introgresi Gen CsNitr1-L dari Transgenik Nipponbare ke Ciherang dan Analisis Pewarisannya pada Generasi BC3F4 - ,, Nazarudin; ,, Suharsono; ,, Sustiprijatno (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2014)
ABSTRACTCsNitr1-L gene is a gene encoding nitrites transporter and is included in the group of proton oligopeptide transporter (POT) gene family. The absorption of nitrites by plants expressing this transporter becomes efficient. The gene encoding this protein (CsNitr1-L) under the control of 35S CaMV Promoter had been introduced into rice plants (Oryza sativa L.) subspecies japonica cv. Nipponbare to transfer this gene. The japonica transgenic rice had been crossed with Ciherang variety followed by back-cross and self polination until BC3F4 generation. The aim of this study was to analyse introgression of CsNitr1-L gene in the transgenic rice BC3F4 generation. The transgenic rice plants in BC3F4 generation were selected based on the resistance to hygromicin. More than 90% population of BC3F4 are putative introgression rice lines carriying the transgene. The introgression of the transgene were indirectly confirmed by PCR analaysis using primer corresponding to hpt gene. The yield of introgression line was higher than these of original Ciherang cultivar. Four introgression lines (G3, G7, G8 and G11) that had higher yield were analysed by PCR. Result of the  analysis showed that these four transgenic plants carried the introgression.Keywords: proton oligopeptide transporter, nitrites transporter, efficient nitrogen, transgenic rice